Targeting Multiple End Organs in Lupus and Other Systemic Rheumatic Diseases by Inhibiting Bruton’s Tyrosine Kinase - Du, Yong; Lei, Ling; Ding, Huihua; Chen, Yanping; Pathak, Simanta; Hicks, John; Tran, Phuongthy T.; Wu, Minghua; Chang, Betty; Wirtz, Uwe; Mohan, Chandra (Frontiers in Immunology, 2022)
Bruton tyrosine kinase (Btk) plays a vital role in activating and differentiating B-cells and regulating signaling in myeloid cells. Indeed, the potential use of Btk inhibitors in preventing lupus has been reported. Here, we extend these observation to 4 additional models of end-organ inflammation: (a) BWF1 lupus nephritis mice, (b) anti-GBM nephritis, (c) bleomycin induced systemic sclerosis like skin disease, and (d) bleomycin-induced lung disease. In agreement with the previous studies, BTK inhibitor (BTKi) treatment was effective in treating lupus nephritis in terms of reducing renal damage both functionally and histologically, accompanied by significant decrease in proteinuria. Both low-dose and high-dose BTKi profoundly blocked renal disease in the anti-GBM nephritis model, with efficacy that was comparable to that seen with dexamethasone. This study provides the first evidence that BTK inhibition has both therapeutic and preventative effects in bleomycin-induced SSc-like disease, in terms of reducing skin thickness, fibrosis, collagen deposition, and inflammation. Likewise, significantly reduced lung inflammatory cell infiltration was observed after treatment with BTKi. Therapeutic benefit was associated with reduced numbers of macrophages, proliferating macrophages and activated T-cells in the respective injured organs. The observation that these immune cells play key roles in driving end organ inflammation in multiple systemic rheumatic diseases have broad implications for the use of BTKi in managing patients with systemic rheumatic diseases where multiple end organs are afflicted, including lupus and systemic sclerosis.